Honey and its nutritional and anti-inflammatory value - Ranneh, Yazan; Md Akim, Abdah; Ab. Hamid, Hasiah; Khazaai, Huzwah; Fadel, Abdulmannan; Zakaria, Zainul Amiruddin; Albujja, Mohammed; Abu Bakar, Mohd Fadzelly (BioMed Central, 2021)
Inflammation is the main key role in developing chronic diseases including cancer, cardiovascular diseases, diabetes, arthritis, and neurodegenerative diseases which possess a huge challenge for treatment. With massively compelling evidence of the role played by nutritional modulation in preventing inflammation-related diseases, there is a growing interest into the search for natural functional foods with therapeutic and preventive actions. Honey, a nutritional healthy product, is produced mainly by two types of bees: honeybee and stingless bee. Since both types of honey possess distinctive phenolic and flavonoid compounds, there is recently an intensive interest in their biological and clinical actions against inflammation-mediated chronic diseases. This review shed the light specifically on the bioavailability and bioaccessibility of honey polyphenols and highlight their roles in targeting inflammatory pathways in gastrointestinal tract disorders, edema, cancer, metabolic and cardiovascular diseases and gut microbiota.